Production of porous material from solar panels waste glass - Bui Khac, Thach; Truong, Vu; Do Quang, Minh; Ly Cam, Hung; Phan, Tuấn Đình (Vietnam Journal of Science and Technology, 2025)
Porous material presents itself as a viable solution for recycling waste photovoltaic panels. In this study, the feasibility of utilizing waste solar panel glass to produce porous material was assessed by incorporating 10 weight percent (wt.%) CaCO3 and 10 wt.% water glass. A simulation of heating microscope method was utilized to determine the firing temperature for the porous material, ranging from 830 °C to 910 °C. The sintered samples have the specific volumetric density ranging from 0.40 to 0.43 g/cm3, water absorption ranging from 171.1 to 202.7 wt.% and apparent porosity of 76.1 to 78.2 %. The morphology of the porous material samples fired at various temperatures demonstrates that the pores’ structure is interconnected. The X-Ray Diffraction (XRD) patterns show that the porous material contains a glassy phase and an impurity one like Devitrite. The findings show that the porous glass not only holds water well, but it is also easy to be re-wetted. Therefore, the porous glass exhibits potential for use as a water-retaining medium, finding applications in various fields, including hydroponics and aquaponics.